The Rupture of Thin Liquid Films Placed on Solid and Liquid Substrates in Gravity Body Forces (Communications in Computational Physics, 2018)
This paper presents a numerical and experimental study on hydrodynamicbehavior of thin liquid films in rectangular domains. Three-dimensional computersimulations were performed using the lattice Boltzmann equation method (LBM). Theliquid films laying on solid and liquid substrates are considered. The rupture of liquidfilms in computations is initiated via the thermocapillary (Marangoni) effect byapplying an initial spatially localized temperature perturbation. The rupture scenariois found to depend on the shape of the temperature distribution and on the wettabilityof the solid substrate. For a wettable solid substrate, complete rupture does not occur:a residual thin liquid film remains at the substrate in the region of pseudo-rupture. Fora non-wettable solid substrate, a sharp-peaked axisymmetric temperature distributioninduces the rupture at the center of symmetry where the temperature is maximal. Axisymmetrictemperature distribution with a flat-peaked temperature profile initiatesrupture of the liquid film along a circle at some distance from the center of symmetry.The outer boundary of the rupture expands, while the inner liquid disk transformsinto a toroidal figure and ultimately into an oscillating droplet.We also apply the LBM to simulations of an evolution of one or two holes in liquidfilms for two-layer systems of immiscible fluids in a rectangular cell. The computedpatterns are successfully compared against the results of experimental visualizations.Both the experiments and the simulations demonstrate that the initially circular holesevolved in the rectangular cell undergoing drastic changes of their shape under theeffects of the surface tension and gravity. In the case of two interacting holes, thedisruption of the liquid bridge separating two holes is experimentally observed andnumerically simulated.